Exercise Attenuates Brain Aging by Rescuing Down-Regulated Wnt/β-Catenin Signaling in Aged Rats - Chen, Dandan; Zhang, Ying; Zhang, Meng; Chang, Jingru; Zeng, Zhenzhong; Kou, Xianjuan; Chen, Ning (Frontiers in Aging Neuroscience, 2020)
Wnt/β-catenin signaling modulates neuronal function and synaptic plasticity. The down-regulated Wnt signaling is involved in aging and Alzheimer’s disease (AD) associated with declined cognitive capacity. However, the molecular mechanisms are still unclear. Herein, we constructed naturally aged rat model by feeding the rats from 6 months to 21 months. The decline in cognitive function of the aged rats was compared with young rats as the controls. Three exercise models (treadmill running, resistance exercise, and alternating exercise with resistance exercise and treadmill running) were applied for intervening aged rats for 12 consecutive weeks to mitigate cognitive impairment. In the present study, Wnt signaling in hippocampal tissues of aged rats with 24 months old and young control rats with 6 months old was examined. Compared with the control, the expression of Dickkopf-1 (DKK-1) as an antagonist of Wnt signal pathway, the activation of GSK-3β, and the hyperphosphorylated Tau were markedly increased as the extension of age. Similarly, higher phosphorylation of β-catenin at Ser33, Ser37 and Thr41 promoted the degradation in aged rats. However, 12 weeks treadmill running could result in a significant decrease in DKK-1, GSK-3β activation, and β-catenin phosphorylation at Ser33, Ser37 and Thr41, as well as hyperphosphorylated Tau. Three intervention models could rescue the abnormal expression of DKK-1 and synaptophysin such as PSD-93 and PSD-95 in hippocampal tissues of the aged rats. In addition, the down-regulation of PI3K/AKT signaling along with Wnt down-regulation in aged rats was observed. Interestingly, resistance exercise and treadmill running could reverse these changes, but alternating exercise with resistance exercise and treadmill running only restored PI3K/Akt signal pathway. Furthermore, the aged rats showed an increase in neuronal loss in hippocampal tissues as shown in an increase in Bax and lower Bcl-2 protein level. In contrast, treadmill running increased Bcl-2 protein level and decreased Bax. Taken together, down-regulated Wnt signaling suppressed PI3K/Akt signal pathway, aggravated synaptotoxicity, induced neuron apoptosis, and accelerated cognitive impairment in aged rats. Three exercise intervention models, especially treadmill running, can attenuate brain aging process of naturally aged rats via restoring Wnt signaling and corresponding targets.